2022
DOI: 10.1590/fst.68720
|View full text |Cite
|
Sign up to set email alerts
|

Development of fresh and dried noodle products with high resistant starch content from banana flour

Abstract: The functional properties, resistant starch (RS), and glycemic index (GI) of fresh noodles substituted with banana flour (BF) were investigated. When the substitution with BF was increased from 0 to 40%, the viscoelastic properties increased, while tensile strength and elasticity decreased from 53.23 to 26.84 g f and 44.65 to 15.04 mm, respectively. GI was reduced from 77.05 to 62.62 while RS content increased from 5.56 to 23.31%. This is considered a very high RS content and the modified noodles are classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, F1 and F3 had a significant difference from the other samples. The highest rehydration rate was in the control formulation, (Tangthanantorn et al, 2021). Generally, a higher water rehydration rate is a desirable property for noodle products (Hastuti et al, 2021).…”
Section: Hardness Of Noodlesmentioning
confidence: 94%
See 1 more Smart Citation
“…However, F1 and F3 had a significant difference from the other samples. The highest rehydration rate was in the control formulation, (Tangthanantorn et al, 2021). Generally, a higher water rehydration rate is a desirable property for noodle products (Hastuti et al, 2021).…”
Section: Hardness Of Noodlesmentioning
confidence: 94%
“…The supplementation of pasta products with high RS flour affects their microstructure, increasing pore sizes, as is evident in scanning electron microscopy (SEM) analyses (Han et al, 2021). Several studies have been carried out on the effects of supplementing pasta products with specific starchy vegetable flour high in resistant starch content (noodles) (Tangthanantorn et al, 2021). However, limited research has been carried out on the effects on noodles of combining several starchy vegetable flours containing resistant starch.…”
Section: Introductionmentioning
confidence: 99%
“…This result was similar to the trend of previous studies, which found that the addition of hydrocolloids (xanthan gum, guar gum, etc.) increased the hardness, adhesiveness, chewiness and resilience of the noodles [ 10 , 11 ]. The increase in hardness and chewiness of the noodles was beneficial in enhancing the noodles’ texture and strength [ 13 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Cooking loss rate is often used as an indicator to evaluate the cooking characteristics of noodles [ 10 ]. As can be seen in Figure 2 , the cooking loss of the noodles increased from 5.25% to 5.43% after adding TF.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation